Open tray impression technique using a silica-nylon mesh for splitting implants: a case report - Paes-Junior, Tarcisio José de Arruda; Freitas, Paolo; Nishioka, Renato Sussumu; Nishioka, Gabriela Nogueira de Melo; Nakano, Leonardo Jiro Nomura (ARCHIVES OF HEALTH INVESTIGATION, 2021)
This article describes an alternative open tray technique for implant impressions using a novel reinforced silica-nylon mesh covered with acrylic resin as a splitting system in assembling the abutment complex. The purpose of the procedure is to simplify the technique and improve the resin contraction during clinical procedure, and also optimizes and reduces the chairside time for the patient. The clinical report was supported by an in vitro study where an analysis tool, Strain Gauge Analysis, was used to prove the clinical effectiveness of the technique. The peri-implant strain was determined on polyurethane casts with the torqued prosthesis, and statistically there was no difference in strain under torque of transfers or in the final prosthesis. The nylon mesh attached to acrylic resin represents a promising option for open tray impression technique, creating a resistant union to transfer in an excellent procedure time.